Reviews (Res Medica, 2014)
• Behaviour of the Human Ureter in Health and Disease James Ross / Peter Edmond / Ian Kirkland Churchill-Livingstone 1972. £3.50• Medical Treatment, a Textbook of Therapy in Four Volumes Volume VI. K. Maclean & G. Scott J. & A. Churchill, London 1971. £2.25.• Proceedings of the Symposium on Epidural Analgesia in Obstetrics• 1972, London Editor, Andrew Doughty, M.B., B.S., F.F.A.R.C.S. Published by H. K. Lewis & Co. Ltd. London. Price £1.50